2018
DOI: 10.1186/s12909-018-1257-4
|View full text |Cite
|
Sign up to set email alerts
|

The importance of scientific competencies in German medical curricula - the student perspective

Abstract: BackgroundScientific competencies are of great importance for physicians; not only for conducting reliable research, but also for patient care. However, there is growing concern that a lack of scientific competencies among physicians may lead to a deterioration in the quality on biomedical research. This study aims at assessing medical students’ perspectives on the implementation of scientific competency training in German medical curricula.MethodsAn online survey was conducted in order to collect German medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 21 publications
7
36
1
2
Order By: Relevance
“…Study results have indicated that medical students vary with respect to their interests in research and a considerable portion of the students prefer special programs for the ones who are strongly interested in research in addition to scienti c core curriculum. Thus, these results support the volunteerbased program approach [10,26]. Moreover, di culties related to mentoring and funding revealed by this study also re ects that only voluntary approaches are applicable for similar faculties.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Study results have indicated that medical students vary with respect to their interests in research and a considerable portion of the students prefer special programs for the ones who are strongly interested in research in addition to scienti c core curriculum. Thus, these results support the volunteerbased program approach [10,26]. Moreover, di culties related to mentoring and funding revealed by this study also re ects that only voluntary approaches are applicable for similar faculties.…”
Section: Discussionsupporting
confidence: 81%
“…Intense competition for training posts makes research experience an important commodity [8]. Furthermore, in some countries like Germany, it is mandatory for medical students to submit a thesis outlining the results of a research project in order to graduate with the title "Doctor" [26][27]. In countries such as Turkey, where scienti c competence does not provide a competitive advantage for residency, nor conducting a research project brings any title to medical undergraduates, motivating students to be involved in a research and integrating research training into medical education are very challenging tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show comparable results [35] and indicate that other didactic concepts similar to the Charité scientific term paper module in the MCM promote a positive attitude among students towards research generally and motivate them to conduct further scientific research [36][, [37]. This finding is consistent with observations from a national survey of medical students by Ratte et al, in which the majority of participants felt that scientific competencies were highly important for their subsequent medical activity and were in favour of the implementation of a project module or scientific term paper in medical education [38]. …”
Section: Discussionsupporting
confidence: 81%
“…Study results have indicated that medical students vary with respect to their interests in research and a considerable portion of the students prefer special programs for the ones who are strongly interested in research in addition to scienti c core curriculum. Thus, these results support the volunteer-based program approach [10,26]. Moreover, di culties related to mentoring and funding revealed by this study also re ects that only voluntary approaches are applicable for similar faculties.…”
Section: Discussionsupporting
confidence: 80%
“…Intense competition for training posts makes research experience an important commodity [8]. Furthermore, in some countries like Germany, it is mandatory for medical students to submit a thesis outlining the results of a research project to graduate with the title "Doctor" [26][27]. In countries such as Turkey, where scienti c competence does not provide a competitive advantage for residency, nor conducting a research project brings any title to medical undergraduates, motivating students to be involved in a research and integrating research training into medical education are very challenging tasks.…”
Section: Introductionmentioning
confidence: 99%